Why Pay NGOs to Involve the Community? - Ronelle Burger; Indraneel Dasgupta; Trudy Owens (Institute for the Study of Labor (IZA), 2014)
We examine the case for donors providing financial incentives to NGOs to increase community participation. We show that, when such incentives are provided, there need not exist any meaningful relationship between beneficiary welfare and the extent of community participation implemented by an NGO. Higher community participation is consistent even with reduced beneficiary welfare. Thus, eliminating community participation from the set of conditions for funding an NGO may improve beneficiary welfare. We provide evidence from the NGO sector in Uganda consistent with our theoretical conclusions. Beneficiaries themselves do not appear to perceive community participation as generating appreciable value-addition in project output.
Keywords: I38; L31; L38; 330; regulation of non-governmental organizations; developing countries; community participation; Uganda